St James and the Good Shepherd: windows on the landscape - Addison, Paul A (Architectural History Aotearoa, 2021)
Two New Zealand churches completed in the 1930s, St James’ Church at Franz Josef/Waiau (James Stuart Turnbull and Percy Watts Rule, 1931) and the Church of the Good Shepherd on the shores of Lake Tekapo (Richard Strachan De Renzy Harman, 1935), feature large plate glass windows behind the altar, affording expansive views of the natural landscape beyond. This represented a significant departure from prevailing ecclesiastical design ideas of the time, with the interior of the churches being intimately connected to the landscape outside, rather than the usual largely internalized atmosphere with any sense of the surroundings limited to light coming through strategically placed decorative or stained-glass windows. It is, however, a design aesthetic that has seldom been utilized in New Zealand since. This paper traverses the history and design of the two churches and their relationships with the landscapes in which they are situated, and concludes that St James’ Church provides a heightened religious experience and is a more successful metaphor for the Christian journey.